Microbial oxidation and assimilation of propylene. - Cerniglia, C E (1976)
Hydrocarbon-utilizing microorganisms in our culture collection oxidized propylene but could not utilize it as the sole source of carbon and energy. When propane-grown cells of Mycobacterium convulutum were placed on propylene, acrylate, the terminally oxidized, three-carbon unsaturated acid, accumulated. A mixed culture and an axenic culture (strain PL-1) that utilized propylene as the sole source of carbon and energy were isolated from soil. Respiration rates, enzyme assays, fatty acid profiles, and 14CO2 incorporation experiments suggest that both the mixed culture and strain PL-1 oxidize propylene via attack at the double bond, resulting in a C2+C1 cleavage of the molecule.